TINJAUAN YURIDIS KEBERADAAN BANDAR UDARA SULTAN SYARIF KASIM II BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 10 TAHUN 2018 TENTANG RENCANA TATA RUANG WILAYAH PROVINSI RIAU TAHUN 2018-2038 - Kiki Amelia Eflin; Mexsasai Indra; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The existence of the Sultan Syarif Kasim II airport, which is currently inthe middle of Pekanbaru City, of course, dramatically influences the spatialplanning of the Pekanbaru City area. This condition will cause urban land use inPekanbaru to become less than optimal. The purpose of writing this thesis is, first,to find out the whereabouts of the Sultan Syarif Kasim II airport based on theRegional Regulation of the Riau Province Number 10 of 2018 concerning the RiauProvince Regional Spatial Plan for 2018-2038. Second, to find a bright spot for theRegional Government in relocating the existence of the Sultan Syarif Kasim IIairport.This type of research is sociological, legal research conducted at theRegional Development Planning Agency of Riau Province, Commission IV of theRegional People's Representative Council of Riau Province, and the Meteorology,Climatology, and Geophysics Agency (BMKG). The population and sample usedare all parties related to the problems studied in this study.The results of this study indicate the existence of Sultan Syarif Kasim IIAirport, which wants to be developed into a primary-scale collector airport thatserves passengers with a total of 5,000,000 (five million) people per year.Construction and development at the current airport location are not feasiblebecause the land is narrow or there is no space to develop the airport to remain inthis location. Therefore it is necessary to relocate the existence of Sultan SyarifKasim II Airport. The government's obstacles in relocating the airport arelocation factor, land condition and land slope factor, land acquisition factor, winddirection, wind speed factor, and budget factor. The government must coordinatewith Angkasa Pura II and equate the perception of the concept of the RegionalSpatial Plan (RTRW) and the Flight Operations Safety Area (KKOP) so that itruns synergistically. The government must immediately make a regulation in theform of a Detailed Spatial Plan (RDTR), which regulates the height of thebuilding and the Basic Coefficient of Buildings and Extraordinary Events aroundthe Sultan Syarif Kasim II Airport area.Keywords: Airport-Spatial planning